Impact of dietary magnesium intake on depression risk in American adults: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2020 - Huang, Yanping; Ruan, Su; Yang, Yang; Liang, Hui; Chen, Su; Chang, Qing (Frontiers in Nutrition, 2025)
IntroductionDepression is a major global mental health challenge. Previous research suggests a link between magnesium consumption and depression, but the dose–response relationship remains unclear. This study investigates the relationship between dietary magnesium intake and depression risk among American adults.MethodsData from the 2005–2020 National Health and Nutrition Examination Survey (NHANES) were examined. Depression was measured with the Patient Health Questionnaire-9 (PHQ-9), and dietary magnesium consumption was calculated from two 24-h meal recalls. We used restricted cubic spline models, logistic regression, and sensitivity analyses to assess the connection.ResultsAmong 35,252 participants (mean age: 49.5 ± 17.6 years; 49.9% women), we observed a nonlinearity in the relationship between dietary magnesium intake and depression. Below the inflection point (366.7 mg/day), the odds ratio (OR) was 0.998 (95% CI: 0.997–0.999, p < 0.001). Above this point, the OR was 1.001 (95% CI: 1.000–1.002, p = 0.007). In participants aged ≥60 years, the association was inverse L-shaped, with magnesium intake ≥270.7 mg/day increasing depression incidence by 0.1% per 1 mg/d increase.ConclusionA nonlinear dose–response relationship exists between dietary magnesium intake and depression risk among US adults. Age significantly moderates this association, suggesting dietary recommendations should be tailored to different age groups.